Performance of the Secretariat of the House of Representatives Ciamis Regency - Devi Tya Noviyanti; Usep Indra Irawan; Irfan Nursetiawan (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2023)
The research conducted on the performance of the Ciamis Regency DPRD Secretariat was motivated by the still low percentage of achieving benefits from DPRD Secretariat activities in 2022 by 71.43% of the target. Of course, this is due to the performance in terms of human resources in the Secretariat of the DPRD Ciamis not optimal in carrying out their duties and functions. The method used in this study is a descriptive research method with a qualitative approach, data collection techniques used by the author in this study are literature studies and field studies consisting of observations, interviews, and documentation. Meanwhile, data analysis techniques are carried out by data reduction, data processing, drawing conclusions and verification. Based on the results of the study it is known that the performance of the DPRD Secretariat Ciamis is quite good, although in practice there are still some indicators of performance that is not optimal.